Letter to a Jewish Friend. - Svidercoschi, Gian Franco (New York The crossroad Publishing Company, 1993)
This haunting, poignant story of the extraordinary and beautiful friendship between Jerzy Kluger and Karol Woityla, a friendship deepened , not lessened, by Karol Woitylas becoming Pope John Paul 2, is itself a paradigm of the Anti-Defamation Leagues relationship with the Catholic Church.
Keywords: Fiction